Processing and characterization of B-based self-sustaining high temperature (SHS) reactive materials and combustion studies - See Toh, Justin Wai Hong. (2009)
B powders are commonly used as fuel in propellants due to their high theoretical gravimetric heat of combustion. However, the formation of viscous B2O3 layer during B combustions acts as a passivating layer that hinders the combustion efficiency.